Lithium metal battery electrolyte, preparation method and application thereof
By adopting a new electrolyte formula in lithium metal batteries, using a variety of lithium salts and ester solvents to form a stable solid electrolyte interface film, the problems of stability and cycle life of lithium metal batteries are solved, and a higher capacity retention rate is achieved and longer cycle life.
Patent Information
- Application Number
- CN202411481457.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
AI Technical Summary
Existing lithium metal batteries face problems of stability and cycle life, mainly due to the growth of lithium dendrites and the high reduction activity of electrolyte components, the solid electrolyte interface film is unstable, which in turn aggravates the depletion of metal lithium and organic electrolytes.
A new lithium metal battery electrolyte formula is adopted, including lithium hexafluorophosphate, lithium bistrifluoromethanesulfonimide, lithium difluorosulfonimide, lithium difluorooxalic acid borate and lithium nitrate, and equal volume of ester is added at an equal molar concentration. In solvent-like, a stable solid electrolyte interface film is formed.
This electrolyte improves the coordination ability between lithium ions and anions, promotes the desolvation process of lithium ions, forms a stable and strong ion-conducting solid electrolyte interface film, reduces side reactions, inhibits the formation of lithium dendrites, and significantly improves lithium The cycle life and capacity of metal batteries are maintained.
Smart Images

Figure CN119400964A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to lithium batteries, and specifically relates to a lithium metal battery electrolyte, a preparation method and an application thereof. Background Art
[0002] The development of electric vehicles has put forward an urgent requirement for high energy density of rechargeable batteries. However, the energy density of commercial lithium-ion batteries with graphite anode is almost close to the theoretical limit. Metal lithium anode with ultra-high specific capacity is rapidly becoming one of the most promising high energy density energy storage devices. However, reliable and stable lithium metal batteries still face great challenges. The growth of lithium dendrites and the high reduction activity of electrolyte components hinder the formation of a stable solid electrolyte interface film. This aggravates the depletion of metal lithium and organic electrolyte, resulting in rapid capacity decay during battery cycling. In addition, the irreversible growth of lithium dendrites may pierce the separator, resulting in thermal runaway behavior of the battery.
[0003] A stable solid electrolyte membrane can be constructed by adjusting the solvation structure of the electrolyte. For this purpose, people have explored a variety of new electrolytes, including high-concentration electrolytes, local high-concentration electrolytes, and fluorinated solvents. Among them, high-concentration electrolytes and local high-concentration electrolytes have a higher concentration of lithium salts, forming a strong Li + The anion coordination clusters stand out. More anions enter the solvation structure of lithium ions and are preferentially reduced to form a robust and inorganic-rich solid electrolyte interface film, thereby reducing the side reactions on the interface. However, these two types of electrolytes are more expensive due to the increased lithium salt concentration. In addition, the fluorinated ether dilution solvents in the locally high-concentration electrolyte will corrode the lithium metal negative electrode and are easily volatile at high temperatures, further deteriorating the battery performance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a lithium metal battery electrolyte, a preparation method and applications thereof.
[0005] A lithium metal battery electrolyte comprises lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium nitrate; the molar concentration ratio of the lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium nitrate is 1:1:1:1:1.
[0006] Preferably, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate are also included.
[0007] Preferably, the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1.
[0008] A method for preparing a lithium metal battery electrolyte comprises the following steps: Lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium nitrate are added to a mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, stirred and dissolved to obtain an electrolyte.
[0009] Preferably, the stirring time is 12 hours.
[0010] Preferably, the molar concentration ratio of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate and lithium nitrate is 1:1:1:1:1.
[0011] Preferably, the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1.
[0012] Application of the above electrolyte or the electrolyte prepared by the above preparation method in the production of lithium metal batteries.
[0013] The lithium metal battery electrolyte provided by the present invention and its preparation method and application mainly have the following beneficial effects: The present invention provides a novel electrolyte formula, which only needs to be prepared by adding five lithium salts in equal molar concentrations to three ester solvents of equal volume. The concentration of the lithium metal electrolyte is 1 mol / L, the cost is low, and the preparation method is simple and controllable, which can be produced on a large scale and is suitable for industrial application.
[0014] Compared with commercial systems, the above-mentioned lithium metal electrolyte will improve the coordination ability between lithium ions and anions due to the introduction of various lithium salts, allowing more anions to enter the solvation sheath of lithium ions and accelerate the desolvation process of lithium ions on the lithium metal surface.
[0015] The lithium metal battery electrolyte can form a solid electrolyte interface film rich in inorganic substances on the surface of metallic lithium. This interface film is stable and has strong ion conductivity, which can reduce the side reaction between the electrolyte and the lithium negative electrode and accelerate the transmission kinetics of lithium ions. This inhibits the formation of lithium dendrites and the generation of dead lithium, and further improves the cycle life and capacity retention of lithium metal batteries.
[0016] The lithium metal battery electrolyte is used for Li||LiNi 0.5 Co 0.2 Mn 0.3 O 2 Full battery, in which LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery has a high load capacity. The capacity retention rate of the battery is greater than 95% under a long cycle of 150 cycles with a current density of 0.2 C and a voltage range of 2.8-4.3 V, which has the potential for market application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure or the prior art, the following will describe the embodiments of the present disclosure or the prior art. The accompanying drawings required for the examples or prior art descriptions are briefly introduced. Obviously, For ordinary technicians in this field, without paying creative work, they can also obtain Get other attached pictures. Figure 1 Li||LiNi constructed from the electrolytes of Example 1 and Comparative Example 1 0.5 Co 0.2 Mn 0.3 O 2 Cycle-to-capacity plot of the full cell obtained during long cycling at room temperature with a current density of 0.2 C and a voltage range of 2.8-4.3 V.
[0018] Figure 2 Li||LiNi constructed using the electrolytes of Example 1 of the present invention and Comparative Example 1 0.5 Co 0.2 Mn 0.3 O 2 Rate performance of the full cell obtained during long cycling at room temperature using a current density of 0.1 C-2 C and a voltage range of 2.8‑4.3 V.
[0019] Figure 3 The Li||Li symmetric battery constructed with the electrolytes prepared in Example 1 and Comparative Example 1 was charged at 1 mA cm −2 Capacity-voltage diagram of current and current density.
[0020] Figure 4 The Coulombic efficiency of the Li||Cu battery constructed with the electrolytes prepared in Example 1 and Comparative Example 1 in lithium plating / stripping was evaluated by the Auerbach method. Specifically, 3 mAh cm −2 of lithium, then at 0.5 mA cm −2 The stripping was completed to 1 V at 0.5 mA cm −2 3 mAh cm −2 The lithium reservoir was again deposited onto a copper substrate and subjected to 0.5 mA cm −2 1 mAh cm-2 for lower cycle stripping / plating −2 Finally, at 0.5 mA cm −2 Under the same conditions, the lithium on the copper substrate was completely stripped to 1 V after 20 cycles.
[0021] Figure 5Li|| LiNi prepared using the electrolytes prepared in Example 1 and Comparative Example 1 0.5 Co 0.2 Mn 0.3 O 2 SEM images of the lithium metal negative electrode obtained after long cycling of the full battery at room temperature with a current density of 0.2 C and a voltage range of 2.8-4.3 V, where a and b are SEM images of the lithium metal negative electrode using the electrolytes of Experimental Example 1 and Comparative Example 1, respectively.
[0022] Figure 6 The Li||Li symmetric battery constructed using the electrolytes prepared in Example 1 and Comparative Example 1 was heated to 10 −2 Hz to 10 6 Impedance plot for the frequency range and 10 mV voltage amplitude test.
[0023] Figure 7 The Li||Cu battery constructed using the electrolytes prepared in Example 1 and Comparative Example 1 was charged at 1 mAh cm at room temperature. −2 After three short cycles at a current density of 1.5447 W, lithium was deposited on the Cu surface. After disassembling the battery, the composition of the Cu surface was analyzed using X-ray photoelectron spectroscopy to obtain the atomic ratio of organic matter to inorganic matter. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1 In a glove box filled with high-purity argon, lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium nitrate were added at a concentration of 0.2 mol / L to a mixed solution of equal volumes of three ester solvents, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and then stirred in the glove box for 12 h until the lithium salt was fully dissolved to obtain the electrolyte.
[0026] Comparative Example 1 The difference between Example 1 and Comparative Example 1 is that the solute in the comparative example is 1 mol / L lithium hexafluorophosphate, and the other conditions are the same as those in Example 1. Comparative Example 1 is a commonly used commercial electrolyte system.
[0027] Battery construction: The positive electrode has a high loading capacity of 3 mAh cm−2 LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Croode), the negative electrode uses 400 μm thick pure lithium Construction of full battery (button-type full battery): stack the CR2032 (Croode) positive electrode shell, 0.5 mm gasket, the prepared positive electrode sheet (Φ10 mm), and PP separator (Φ16 mm) in the middle in sequence, then add 80 μL of the corresponding electrolyte, and after it wets the separator, stack the pure lithium negative electrode (Φ14 mm), 0.5 mm gasket, spring, and negative electrode shell in the middle in sequence, and finally place the whole into the battery sealing machine for compaction and let it stand for 12 h before use.
[0028] like Figure 1 As shown, the Li|| LiNi electrolyte constructed by Example 1 of the present invention and Comparative Example 1 0.5 Co 0.2 Mn 0.3 O 2 The cycle number-specific capacity diagram obtained during the long cycle of the full battery at room temperature with a current density of 0.2 C and a voltage range of 2.8-4.3 V. It can be seen that the lithium metal battery constructed in Comparative Example 1 is unstable, with obvious capacity decay after 30 cycles and a capacity drop after 55 cycles. However, the lithium metal battery in Example 1 can be cycled stably, and still has a capacity retention rate of more than 95% after 150 cycles.
[0029] like Figure 2 As shown, the Li||LiNi electrolyte constructed by Example 1 of the present invention and Comparative Example 1 0.5 Co 0.2 Mn 0.3 O 2 The rate performance diagram of the full battery obtained during the long cycle process with a current density of 0.1 C-2 C and a voltage range of 2.8-4.3 V at room temperature. Compared with Comparative Example 1, Example 1 shows the best rate performance, and can still maintain 130 mAh g at a large charge and discharge current density of 2 C. −1 The specific capacity of the comparative example 1 was 0.1 C, and it could still cycle stably when the current density returned to 0.1 C. However, as the current density increased, the capacity of the comparative example 1 showed obvious attenuation, and it could not cycle stably when it returned to the initial current density of 0.1 C.
[0030] like Figure 3 As shown, the Li||Li symmetric battery (lithium-lithium symmetric battery refers to a button-type battery, which is constructed in the same way as the full battery, with negative electrode material||negative electrode material) constructed with the electrolytes prepared in Example 1 of the present invention and Comparative Example 1 is 1 mA cm −2Time-voltage diagram of current density. It can be observed that after 150 h of cycling, comparative example 1 showed a significant increase in polarization. Due to severe dendrite growth and side reactions, the battery resistance increased sharply. In contrast, example 1 can be stably cycled for more than 300 h, which indicates that a stable lithium negative electrode interface is formed in example 1, which enhances the reversibility of lithium deposition and stripping and effectively inhibits the growth of lithium dendrites. like Figure 4 As shown, the Li||Cu battery constructed with the electrolyte prepared in Example 1 of the present invention and Comparative Example 1 was evaluated for the Coulombic efficiency of lithium plating / stripping by the Auerbach method. −2 and the equivalent capacity is 1 mAhcm −2 After 20 cycles under the conditions of , the electrolyte of comparative example 1 showed unstable cycling, indicating that its compatibility with the lithium metal anode was poor. The average coulombic efficiency of example 1 reached 99.1%, indicating that the reversibility of the lithium metal anode was significantly enhanced. like Figure 5 As shown, the Li||LiNi electrolyte prepared by using the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention is shown. 0.5 Co 0.2 Mn 0.3 O 2 The full battery is at room temperature, using a current density of 0.2 C, and a voltage range of 2.8-4.3 V. The scanning electron microscope image of the lithium metal negative electrode obtained after long cycling, where a and b are the scanning electron microscope images of the lithium metal negative electrode using the electrolyte of Experimental Example 1 and Comparative Example 1, respectively. Example 1 forms a uniform lithium deposition morphology, while Comparative Example 1 forms a distinct dendritic lithium deposition morphology. This shows that Example 1 produces fewer side reactions and suppresses the dendritic behavior of lithium.
[0031] like Figure 6 As shown, the Li||Li symmetrical battery constructed by using the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention is constructed at room temperature with 10 −2 Hz to 10 6 Hz frequency range and 10 mV voltage amplitude test impedance diagram. It can be observed that the charge transfer impedance of Example 1 is significantly lower than that of Comparative Example 1. The smaller charge transfer impedance indicates that the desolvation barrier of lithium ions in Example 1 is reduced, so that the desolvation process of lithium ions on the lithium metal surface is accelerated.
[0032] like Figure 7 As shown in the figure, the Li||Cu battery constructed using the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention has a capacity of 1 mAh cm −2After three short cycles of current density, lithium was deposited on the Cu surface. After disassembling the battery, the composition of the Cu surface was analyzed using X-ray photoelectron spectroscopy. It can be observed that compared with Comparative Example 1, the SEI of Example 1 includes more inorganic matter and less organic matter. This indicates that more anions enter the solvation sheath of lithium ions, and these anions will preferentially be reduced to inorganic matter on the lithium metal surface and passivate the solid electrolyte interface film and accelerate the transmission of lithium ions in the interface film, thereby reducing electrolyte side reactions and inhibiting the growth of lithium dendrites, and finally achieving stable circulation of lithium metal batteries.
[0033] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0034] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A lithium metal battery electrolyte, characterized in that: It includes lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalate borate and lithium nitrate; the molar concentration ratio of the lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalate borate and lithium nitrate is 1:1:1:1:
1.
2. The lithium metal battery electrolyte according to claim 1, characterized in that Also included are ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
3. The lithium metal battery electrolyte according to claim 2, characterized in that The volume ratio of the ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:
1.
4. A method for preparing a lithium metal battery electrolyte, characterized in that: The following steps are involved: Lithium hexafluorophosphate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate and lithium nitrate are added to a mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, stirred and dissolved to obtain an electrolyte.
5. The method for preparing a lithium metal battery electrolyte according to claim 4, characterized in that: The stirring time is 12h.
6. The method for preparing a lithium metal battery electrolyte according to claim 4, characterized in that: The molar concentration ratio of the lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate and lithium nitrate is 1:1:1:1:
1.
7. The method for preparing a lithium metal battery electrolyte according to claim 4, characterized in that: The volume ratio of the ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:
1.
8. Use of the electrolyte according to any one of claims 1 to 3 or the electrolyte prepared by the preparation method according to any one of claims 4 to 7 in the production of lithium metal batteries.